BRCA status in epithelial ovarian cancer: implications for management and future clinical trial design. (August 2013) - Konstantinopoulos, Panagiotis A; Matulonis, Ursula A
Despite significant advances in surgical and medical management, epithelial ovarian cancer (EOC) remains the fifth most common cause of cancer death and the most lethal of all gynecologic malignancies in the USA. Given that EOC is a genetically and biologically heterogeneous disease, a personalized approach to management based on recognition of different EOC subtypes with distinct genotypic and phenotypic characteristics may be an effective strategy to improve outcomes in this disease. EOC is characterized by frequent genetic and epigenetic alterations in gene members of the homologous recombination DNA-repair pathway, most commonly in the BRCA1 and BRCA2 genes. Germline BRCA1 and BRCA2 mutations have been identified in approximately 15% of all EOCs while an additional 30–35% of tumors harbor other genetic or epigenetic alterations in the homologous recombination pathway. In this review, we summarize the phenotypic characteristics of BRCA1/2 -associated tumors and their clinical implications, both in terms of routine patient management as well as clinical trial design.